(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This study investigates the microscopic changes occurring in the synchondrosis of the spine under the influence of experimental hypotheriosis. The research employs histological and imaging techniques to assess the structural and cellular alterations within the affected regions. Findings indicate significant degenerative and adaptive transformations in response to prolonged hypothermic conditions, contributing to a deeper understanding of spinal pathophysiology in extreme environments.